Palladium-catalyzed reductive Heck-type vinylative dearomatization of unfunctionalized halonaphthalene derivatives. Issue 102 (24th October 2016) - Dou, Yingchao; Yang, Liting; Zhang, Lu; Zhang, Panke; Li, Heng; Yang, Guanyu
Abstract : A novel strategy for the dearomatization of inactive 1-halonaphthalenes via palladium-catalyzed reductive Heck-type vinylative reaction was successfully developed. Abstract : A novel strategy for the dearomatization of inactive 1-halonaphthalenes via palladium-catalyzed reductive Heck-type vinylative reaction was successfully developed. Both homo- and hetero-cyclic naphthalene derivatives were tolerated, and the desired products were obtained in modest to good yields.